ROOT CAUSE ANALYSIS OF DIESEL GENERATOR BLACKOUT DUE TO FUEL RACK MALFUNCTION ON MV SINAR SORONG - Didik Dwi Suharso (PIP Makassar, 2026)
The electricity of a ship greatly depends on diesel generators, which depend on the fuel system to be effectively combusted. This study examines a ship blackout incident that was occasioned by a huge disparity in exhaust gas temperature in a diesel generator. Data were collected by observing, interviewing, documenting and reviewing the literature using a qualitative descriptive design and Fishbone diagram as a tool of analysis. The root cause of the study has been cited as failure in combustion in one of the cylinders brought about by mechanical slip in the fuel rack system. Results show that problems in the delivery of fuel, including leakages in the pipes, corrosion, stuck fuel racks, and poor monitoring cause imbalances during combustion. Such imbalances increase the exhaust temperatures causing extreme degradation of performance and resultant blackouts. To avoid the occurrence in future, ensure the stability of the generators, and minimize the loss of the economy, this paper can recommend planned preventive maintenance, stringent monitoring schedule, and thorough documentation, so that the fuel system has the best safety.